Posttransfusion Haematocrit Equilibration: Timing Posttransfusion Haematocrit Check in Neonates at the National Hospital, Abuja, Nigeria - L. I. Audu; A. T. Otuneye; A. B. Mairami; L. J. Mshelia; V. E. Nwatah (International Journal of Pediatrics)
Anaemia is a common morbidity in the NICU and often requires transfusion of packed red blood cells. Haematocrit equilibration following red cell transfusion occurs over time ultimately resulting in a stable packed cell volume (PCV). Knowledge of this equilibration process is pertinent in the accurate timing of posttransfusion (PT) PCV. We conducted a prospective study to determine an appropriate timing for PT PCV estimation on 47 stable anaemic babies at the Neonatal Unit of National Hospital, Abuja. Values of PCV were determined before transfusion and at 1, 6, 12, 24, and 48 hours posttransfusion. Forty of the recruited neonates and young infants were analyzed. Their gestational age range was 26 to 40 weeks. 1-hour PT PCV (48.5% ± 5.5%) was similar to the 6-hour PT PCV (47.8% ± 5.6%) P=0.516, but both were significantly different from the 12-hour (46.8% ± 5.9%), 24-hour (45.9 ± 5.8%), and 48-hour (45.4% ± 6.2%) PT PCVs. The 12-hour PT PCV was similar to the 24-hour and 48-hour PT PCVs (P=0.237 and 0.063, resp.). We concluded that, in stable nonhaemorrhaging and nonhaemolysing young infants, the estimated timing of haematocrit equilibration and, consequently, posttransfusion PCV is 12 hours after red blood cell transfusion.